Penanganan Risiko Keamanan Informasi Aplikasi Webmarket Berdasarkan ISO 27001:2013 (Study Kasus pada PT Sanjaya Citra Anugrah) - M. Hadi Prayitno (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2021)
Sanjaya Citra Anugerah (SCA) is a company engaged in the rental and sale of heavy equipment, committed to ensuring the security of organizational information to maintain the confidentiality, integrity and availability of information from the threat of information security failure. This is realized by implementing an information security management system based on the international standard ISO 27001:2013. This study aims to describe the scope of the information security management system, the internal and external factors that influence it and to identify broadly the potential failures of information security and their impact. The potential failure is a risk that must be identified based on current conditions, which will then be determined to cause a risk management plan to be prepared, so that information security can be maintained and ultimately increase the level of trust from stakeholders.